1999
DOI: 10.1089/gte.1999.3.227
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the SLC3A1 Gene in Cystinuric Patients: Frequencies and Identification of a Novel Mutation

Abstract: Cystinuria is a frequent autosomal recessive transport disorder characterized by defective renal resorption of cystine and other dibasic amino acids. Biochemically, three types of cystinuria can be defined. Here we present our results of screening for mutations in the SLC3A1 gene, which codes for a dibasic amino acid transporter protein and appears to be involved in the pathogenesis of cystinuria type I. Our study population consists of 5 Italian cystinuria type I patients and 10 cystinuric patients as yet unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…Previous work leads us to postulate that SLC3A1 mutations are responsible only for type I cystinuria, still mutations in the SLC3A1 gene are not detected in all cystinuria type I patients Horsford et al, 1996;Goodyer et al, 1998;Saadi et al, 1998;Albers et al, 1999]. The patients in the present study were not biochemically classified as type I-or non-type I cystinuria and therefore the absence of mutations in SLC3A1 in some individuals may be explained by mutations in a non-type I cystinuria locus, most likely the recently cloned SLC7A9 gene.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Previous work leads us to postulate that SLC3A1 mutations are responsible only for type I cystinuria, still mutations in the SLC3A1 gene are not detected in all cystinuria type I patients Horsford et al, 1996;Goodyer et al, 1998;Saadi et al, 1998;Albers et al, 1999]. The patients in the present study were not biochemically classified as type I-or non-type I cystinuria and therefore the absence of mutations in SLC3A1 in some individuals may be explained by mutations in a non-type I cystinuria locus, most likely the recently cloned SLC7A9 gene.…”
Section: Discussionmentioning
confidence: 47%
“…To date more than 40 different mutations have been reported in the SLC3A1 gene in cystinuria patients from populations in Italy and Spain [Calonge et al, 1994;Gasparini et al, 1995;Bisceglia et al, 1996;Albers et al, 1999], the Middle East [Pras et al, 1995], Japan [Miyamoto et al, 1995;Egoshi et al, 2000], Canada [Horsford et al, 1996;Saadi et al, 1998], and the United States [Gitomer et al, 1998]. The mutations tend to be population-specific although there are a few that occur worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…This mutation is common in South-eastern European (1718), Gypsy (19), and Greek populations (20) but has not been found in Chinese (21) and Japanese (22) patients. Conversely, the SLC7A9 p.P482L mutation is common in Japanese patients (22), but has not been found in European populations.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we functionally characterized the R365W mutation of human rBAT, which was found in three cystinuria patients [29]; additionally, a mutation to leucine at the same position (R365L) was reported in another patient [34]. Interestingly, the rBAT mutation R365W combines a trafficking defect with altered functional properties of the transporter b 0,+ .…”
Section: Trafficking Defectmentioning
confidence: 92%